Efficacy analysis of the aprepitant-combined antiemetic prophylaxis for non-round cell soft-tissue sarcoma patients received adriamycin and ifosfamide therapy. Issue 49 (December 2016) - Kusaba, Hitoshi; Kumagai, Hozumi; Inadomi, Kyoko; Matsunobu, Tomoya; Harimaya, Katsumi; Takayoshi, Kotoe; Arita, Shuji; Ariyama, Hiroshi; Akashi, Koichi; Baba, Eishi
Abstract : Abstract: Appropriate antiemetic prophylaxis for moderately emetogenic chemotherapy in patients with non-round cell soft-tissue sarcomas (NRC-STS) remains unclear. We retrospectively investigated efficacy and safety of aprepitant-combined antiemetic prophylaxis in patients with NRC-STS receiving adriamycin plus ifosfamide (AI) therapy. Forty NRC-STS patients were enrolled, their median age was 50 years (range 18–74), and 13 (32.5%) were female. Median cycle number of AI therapy was 4. Twenty patients received the doublet antiemetic prophylaxis (5-hydroxytryptamine-3 receptor antagonist and dexamethasone), and 20 received triplet (5-hydroxytryptamine-3 receptor antagonist, dexamethasone, and aprepitant). In the overall period, complete response rate for nausea and emesis in the triplet group was significantly higher than that in the doublet group (70% vs 35%; P = 0.027). Patients with no-emesis in the overall period were more frequently observed in the triplet group than in the doublet group (90% vs 65%; P = 0.058). All toxicities other than emesis were almost equivalent in both the groups. These results suggest that a triplet antiemetic prophylaxis may be optimal in the treatment with AI therapy for NRC-STS.